Sport, stress, and burnout - VERARDI, Carlos Eduardo Lopes (2012)
For many authors, stress is negatively related to individual performance. Some evidence, however, suggests that performance in a given task will be lower under very low or very high levels of stress and great under moderate levels of stress. Burnout is associated with the perception that personal resources are insufficient or inadequate to cope with stress. Identifying stressors and coping strategies which, if used by individuals, can minimize the impact of stress, and allow preventive and intervention programs to be designed. The aim of this study is to present an updated review of burnout within sporting context.